Dietary Reference Intakes: Applications in Dietary Planning - Institute of Medicine (The National Academies Press, 2003)
The Dietary Reference Intakes (DRIs) are quantitative estimates of nutrient intakes to be used for planning and assessing diets for apparently healthy people. This volume is the second of two reports in the DRI series aimed at providing specific guidance on the appropriate uses of the DRIs. The first report provided guidance on appropriate methods for using DRIs in dietary assessment. This volume builds on the statistical foundations of the assessment report to provide specific guidance on how to use the appropriate DRIs in planning diets for individuals and for groups.
Keywords: Food and Nutrition

The Resistance Phenomenon in Microbes and Infectious Disease Vectors: Implications for Human Health and Strategies for Containment: Workshop Summary - Institute of Medicine (The National Academies Press, 2003)
The resistance topic is timely given current events. The emergence of mysterious new diseases, such as SARS, and the looming threat of bioterrorist attacks remind us of how vulnerable we can be to infectious agents. With advances in medical technologies, we have tamed many former microbial foes, yet with few new antimicrobial agents and vaccines in the pipeline, and rapidly increasing drug resistance among infectious microbes, we teeter on the brink of loosing the upperhand in our ongoing struggle against these foes, old and new. The Resistance Phenomenon in Microbes and Infectious Disease Vectors examines our understanding of the relationships among microbes, disease vectors, and human hosts, and explores possible new strategies for meeting the challenge of resistance.
Keywords: Health and Medicine; Food and Nutrition

An Assessment of the CDC Anthrax Vaccine Safety and Efficacy Research Program - Institute of Medicine (The National Academies Press, 2003)
In 1998, the Department of Defense (DoD) began a program of mandatory immunization against anthrax for all military personnel. As the program proceeded, however, some military personnel and their families raised concerns about the safety and efficacy of the anthrax vaccine. Acknowledging both the need to protect military personnel and the concerns about the anthrax vaccine, congress directed the Centers for Disease Control and Prevention (CDC) to carry out a research program on its safety and efficacy. To assist in the development of this program, CDC requested the Institute of Medicine (IOM) to convene a committee to review the completeness and appropriateness of the research program. In An Assessment of the CDC Anthrax Vaccine Safety and Efficacy Research Program, the committee makes an overall assessment of the CDD research plan and reviews the specific studies proposed by CDC in the three areas of efficacy, safety and acceptability. The committee also notes additional research needs that became evident following the bioterrorist events of 2001 and makes recommendations about the leadership of the research program.
Keywords: Health and Medicine; Conflict and Security Issues

Key Capabilities of an Electronic Health Record System: Letter Report - Institute of Medicine (The National Academies Press, 2003)
Commissioned by the Department of Health and Human Services, Key Capabilities of an Electronic Health Record System provides guidance on the most significant care delivery-related capabilities of electronic health record (EHR) systems. There is a great deal of interest in both the public and private sectors in encouraging all health care providers to migrate from paper-based health records to a system that stores health information electronically and employs computer-aided decision support systems. In part, this interest is due to a growing recognition that a stronger information technology infrastructure is integral to addressing national concerns such as the need to improve the safety and the quality of health care, rising health care costs, and matters of homeland security related to the health sector. Key Capabilities of an Electronic Health Record System provides a set of basic functionalities that an EHR system must employ to promote patient safety, including detailed patient data (e.g., diagnoses, allergies, laboratory results), as well as decision-support capabilities (e.g., the ability to alert providers to potential drug-drug interactions). The book examines care delivery functions, such as database management and the use of health care data standards to better advance the safety, quality, and efficiency of health care in the United States.
Keywords: Computers and Information Technology

Scientific Criteria to Ensure Safe Food - Institute of Medicine; National Research Council (The National Academies Press, 2003)
Food safety regulators face a daunting task: crafting food safety performance standards and systems that continue in the tradition of using the best available science to protect the health of the American public, while working within an increasingly antiquated and fragmented regulatory framework. Current food safety standards have been set over a period of years and under diverse circumstances, based on a host of scientific, legal, and practical constraints.
Keywords: Food and Nutrition

Malaria Control During Mass Population Movements and Natural Disasters - National Research Council (The National Academies Press, 2003)
Admittedly, the world and the nature of forced migration have changed a great deal over the last two decades. The relevance of data accumulated during that time period can now be called into question. The roundtable and the Program on Forced Migration at the Mailman School of Public Health of Columbia University have commissioned a series of epidemiological reviews on priority public health problems for forced migrants that will update the state of knowledge. Malaria Control During Mass Population Movements and Natural Disasters -- the first in the series, provides a basic overview of the state of knowledge of epidemiology of malaria and public health interventions and practices for controlling the disease in situations involving forced migration and conflict.
Keywords: Health and Medicine

Who Will Keep the Public Healthy?: Educating Public Health Professionals for the 21st Century - Institute of Medicine (The National Academies Press, 2003)
Bioterrorism, drug--resistant disease, transmission of disease by global travel . . . there’s no shortage of challenges facing America’s public health officials. Men and women preparing to enter the field require state-of-the-art training to meet these increasing threats to the public health. But are the programs they rely on provide the high caliber professional training they require?
Keywords: Health and Medicine

Food Chemicals Codex: Fifth Edition - Institute of Medicine (The National Academies Press, 2003)
Since its first edition in 1966, the Food Chemicals Codex (FCC) has provided the accepted standards for quality and purity in food chemicals, officially referenced by the U.S. Food and Drug Administration and many agencies in other countries. The Fifth Edition updates the field, incorporating the definitive monographs of previous editions with completely new material. Each monograph provides a physical description of the substance and its use in foods, lists its purity requirements, describes the appropriate tests to determine compliance, and provides packaging and storage guidelines. Other features include
Keywords: Food and Nutrition

Twenty-Fourth Symposium on Naval Hydrodynamics - National Research Council (The National Academies Press, 2003)
This report is part of a series of reports that summarize this regular event. The report discusses research developments in ship design, construction, and operation in a forum that encouraged both formal and informal discussion of presented papers.
Keywords: Math, Chemistry, and Physics

Health Professions Education: A Bridge to Quality - Institute of Medicine (The National Academies Press, 2003)
The Institute of Medicine study Crossing the Quality Chasm (2001) recommended that an interdisciplinary summit be held to further reform of health professions education in order to enhance quality and patient safety. Health Professions Education: A Bridge to Quality is the follow up to that summit, held in June 2002, where 150 participants across disciplines and occupations developed ideas about how to integrate a core set of competencies into health professions education.
Keywords: Education; Health and Medicine

Accelerating the Research, Development, and Acquisition of Medical Countermeasures Against Biological Warfare Agents: Interim Report - Institute of Medicine; National Research Council (The National Academies Press, 2003)
Keywords: Conflict and Security Issues

Enhancing the Vitality of the National Institutes of Health: Organizational Change to Meet New Challenges - Institute of Medicine; National Research Council (The National Academies Press, 2003)
The report says that important organizational changes are needed at the National Institutes of Health to ensure the agency meets future challenges effectively. In particular, the report advises NIH to devote additional resources to innovative interdisciplinary research that reflects its strategic objectives and cuts across all agency's institutes and centers. The report recommends that Congress should establish a formal process for determining how specific proposals for changes in the number of NIH agencies and centers should be addressed.
Keywords: Health and Medicine

When Children Die: Improving Palliative and End-of-Life Care for Children and Their Families - Institute of Medicine (The National Academies Press, 2003)
The death of a child is a special sorrow. No matter the circumstances, a child’s death is a life-altering experience. Except for the child who dies suddenly and without forewarning, physicians, nurses, and other medical personnel usually play a central role in the lives of children who die and their families. At best, these professionals will exemplify “medicine with a heart.” At worst, families’ encounters with the health care system will leave them with enduring painful memories, anger, and regrets. When Children Die examines what we know about the needs of these children and their families, the extent to which such needs are—and are not—being met, and what can be done to provide more competent, compassionate, and consistent care. The book offers recommendations for involving child patients in treatment decisions, communicating with parents, strengthening the organization and delivery of services, developing support programs for bereaved families, improving public and private insurance, training health professionals, and more. It argues that taking these steps will improve the care of children who survive as well as those who do not—and will likewise help all families who suffer with their seriously ill or injured child. Featuring illustrative case histories, the book discusses patterns of childhood death and explores the basic elements of physical, emotional, spiritual, and practical care for children and families experiencing a child’s life-threatening illness or injury.
Keywords: Health and Medicine

Guidelines for the Care and Use of Mammals in Neuroscience and Behavioral Research - National Research Council (The National Academies Press, 2003)
Expanding on the National Research Council’s Guide for the Care and Use of Laboratory Animals, this book deals specifically with mammals in neuroscience and behavioral research laboratories. It offers flexible guidelines for the care of these animals, and guidance on adapting these guidelines to various situations without hindering the research process. Guidelines for the Care and Use of Mammals in Neuroscience and Behavioral Research offers a more in-depth treatment of concerns specific to these disciplines than any previous guide on animal care and use. It treats on such important subjects as:
Keywords: Biology and Life Sciences

BIO2010: Transforming Undergraduate Education for Future Research Biologists - National Research Council (The National Academies Press, 2003)
Biological sciences have been revolutionized, not only in the way research is conducted—with the introduction of techniques such as recombinant DNA and digital technology—but also in how research findings are communicated among professionals and to the public. Yet, the undergraduate programs that train biology researchers remain much the same as they were before these fundamental changes came on the scene. This new volume provides a blueprint for bringing undergraduate biology education up to the speed of today's research fast track. It includes recommendations for teaching the next generation of life science investigators, through:
Keywords: Education

Beyond the Molecular Frontier: Challenges for Chemistry and Chemical Engineering - National Research Council (The National Academies Press, 2003)
Chemistry and chemical engineering have changed significantly in the last decade. They have broadened their scope—into biology, nanotechnology, materials science, computation, and advanced methods of process systems engineering and control—so much that the programs in most chemistry and chemical engineering departments now barely resemble the classical notion of chemistry. Beyond the Molecular Frontier brings together research, discovery, and invention across the entire spectrum of the chemical sciences—from fundamental, molecular-level chemistry to large-scale chemical processing technology. This reflects the way the field has evolved, the synergy at universities between research and education in chemistry and chemical engineering, and the way chemists and chemical engineers work together in industry.
Keywords: Math, Chemistry, and Physics; Computers and Information Technology

Gulf War and Health: Volume 2: Insecticides and Solvents - Institute of Medicine (The National Academies Press, 2003)
Gulf War and Health, Volume 2, is the second in a series of congressionally-mandated studies by the Institute of Medicine that provides a comprehensive assessment of the available scientific literature on potential health effects of exposure to certain biological, chemical, and environmental agents associated with the Gulf War. In this second study, the committee evaluated the published, peer-reviewed literature on exposure to insecticides and solvents thought to have been present during the 1990-1991 war.
Keywords: Health and Medicine; Environment and Environmental Studies

The Richard and Hinda Rosenthal Lectures -- 2001: Exploring Complementary and Alternative Medicine - Institute of Medicine; Institute of Medicine (The National Academies Press, 2003)
The Rosenthal lecture included in this volume explores the world of complementary medicine and its implications for medical research, clinical practice, and policy in the United States.
Keywords: Health and Medicine

Responsible Research: A Systems Approach to Protecting Research Participants - Institute of Medicine (The National Academies Press, 2003)
When 18-year-old Jesse Gelsinger died in a gene transfer study at the University of Pennsylvania, the national spotlight focused on the procedures used to ensure research participants' safety and their capacity to safeguard the well-being of those who volunteer for research studies. Responsible Research outlines a three-pronged approach to ensure the protection of every participant through the establishment of effective Human Research Participant Protection Programs (HRPPPs). The approach includes:
Keywords: Health and Medicine

Biographical Memoirs: Volume 83 - National Academy of Sciences (The National Academies Press, 2003)
Biographic Memoirs Volume 83 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography